Optimization of process conditions for Ganoderma lucidum triterpenes production from Panax notoginseng residues by solid-state fermentation - TAN Xiandong, CAI Kunyou, WANG Lang, ZOU Jian, CHEN Xinying, CHEN Xiangchu (Zhongguo niangzao)
The effects of fermentation temperature, inoculum and fermentation time on Ganoderma lucidum triterpenes production from Panax notoginseng residues by the solid-state fermentation were investigated by the single factor tests, and the fermentation process conditions were optimized by response surface method. The results showed that the effects of fermentation temperature, inoculum and fermentation time on G. lucidum triterpenes content were all greatly significant (P<0.01). The effects of the 3 factors on G. lucidum triterpenes content in fermentation culture were ranked as follows: inoculum>fermentation time>fermentation temperature. The interaction between fermentation temperature and inoculum had greatly significant influence on G. lucidum triterpenes content (P<0.01), the effects of interaction between inoculum and fermentation time, and fermentation time and temperature on G. lucidum triterpenes content were not significant (P>0.05). The optimum fermentation conditions in the laboratory were as follows: fermentation temperature 30 ℃, time 16 d, and inoculum 11%. Under these optimal conditions, the G. lucidum triterpenes content was (4.110±0.186) mg/g, which was 12% higher than that before optimization.